Transformation of Customary Law in the Digital Era: Opportunities and Challenges in the Archipelago - Anggia Faradina (PT. Anagata Sembagi Education, 2024)
The transformation of customary law in the digital era faces complex dynamics in the archipelago, where information and communication technology acts as a catalyst for change in various aspects of social and legal life. This article explores how digital advances affect customary law practices and cultural identities in Indonesia, and analyzes the opportunities and challenges that arise from the integration of technology into customary law systems. Using a qualitative approach, this article examines several cases across the archipelago to illustrate how digital technologies such as web-based applications, data management systems, and social media platforms are accelerating the process of customary law transformation. These transformations include the digitization of customary law administration, increased transparency in dispute resolution, and the potential for the preservation and promotion of local culture globally. However, the use of technology also poses significant challenges, such as the risk of loss of cultural authenticity, shifting traditional values, and unequal access to technology in more remote indigenous communities. This article also discusses how a culturally sensitive and inclusive approach can help address these challenges, by providing recommendations for policies and practices that support equitable and effective technology integration. The results of this study show that while digital technology offers opportunities to strengthen and develop customary law, it is important to pay attention to its impact on the social and cultural structures of indigenous communities. A holistic and participatory approach will be key to ensuring that the transformation of customary law in the digital era goes hand in hand with the preservation of cultural values ​​and community rights.